(ab+bc) square-2 ab square c
Answers
Answered by
0
Step-by-step explanation:
(ab+bc)²-2ab²c
∞ So,here will use the identity (a+b)² = a²+b²+2ab
→ (ab)²+(bc)1+2(ab)(bc)-2ab²c
→ a²b²+b²c²+2ab²c-2ab²c
→ a²b²+b²c²
∞ As we know,negative digits can cancel with positive digits(in third step). So,we got the required answer.
SomeImportantIdentities
★ (a+b)²=a²+b²+2ab)
★ (a-b)²=a²+b²-2ab
★ (a²-b²)=(a-b)(a+b)
★ (x+a)(x+b)=x²+(a+b)x+ab
Hope it help you out
Plz Mark me a Brainliest!!!!☺️
Answered by
0
hope helps you make me as brainlist
Attachments:
![](https://hi-static.z-dn.net/files/d59/6b4597795220b9971c5ccd77f0672dc3.jpg)
Similar questions
World Languages,
5 months ago
Science,
5 months ago
Physics,
11 months ago
India Languages,
1 year ago
Math,
1 year ago